(untitled) (ENTHYMEMA, 2012)
Many Amelia Rosselli’s statements establish a strong relationship between her last short poem Impromptu, published in 1981, and Ingeborg Bachmann’s poems. After analysing the documents archived in the Fondo Amelia Rosselli at the Centro di Tradizione Manoscritta di Pavia, we compare here the textual convergences of the two poetic productions and their similar theoretical premises. We will conclude that Rosselli’s inspiration from Bachmann is rather labile and that her insistence in claiming such a genetic ascendance, if on one hand verifies a mainly retrospective correspondence, on the other one belongs to Rosselli’s strategy of constructing an authorial figure.